A ball mill lining and its processing technology

By using materials such as styrene butadiene rubber and modified nano-silicon nitride, combined with refining and vulcanization processes, a ball mill lining with high wear resistance and aging resistance was prepared, which solved the problem of insufficient lining performance in the prior art, and achieved more efficient wear protection and more stable performance.

CN119192697BActive Publication Date: 2025-03-14ZHUZHOU CHANGJIANG SPECIAL MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411731168.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-14
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The wear resistance and aging resistance of existing ball mill linings are insufficient, resulting in a short service life. The common anti-aging agents are poorly compatible with the rubber matrix, which is prone to "blasting frost", which affects performance and aesthetics.

Method used

Styrene-butadiene rubber is used as the matrix, and modified nano-silicon nitride, zinc oxide, initiator, lubricant, sulfur and vulcanization accelerator are added. Through the refining and vulcanization process, a ball mill liner with high wear resistance and aging resistance is prepared.

Benefits of technology

It significantly improves the wear resistance, aging resistance and mechanical properties of the ball mill lining, reduces the occurrence of frost spraying, extends the service life, and improves the stability of performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a ball mill lining and a processing technology thereof, and belongs to the technical field of ball mill linings. The invention comprises the following raw materials in parts by weight: 80-100 parts of styrene-butadiene rubber, 10-20 parts of modified nano silicon nitride, 4-8 parts of zinc oxide, 0.2-0.4 parts of initiator, 2-6 parts of lubricant, 3-5 parts of sulfur, and 0.5-1 parts of vulcanization accelerator. The lining prepared by the invention uses styrene-butadiene rubber as a matrix, which gives the lining certain wear resistance and aging resistance; wherein zinc oxide can make the mechanical properties of the lining after vulcanization higher; wherein the modified nano silicon nitride has good compatibility with the styrene-butadiene rubber matrix, significantly improves the wear resistance, aging resistance and mechanical properties of the lining, and has stable performance, and the frost spraying phenomenon is significantly reduced; therefore, the lining prepared by the invention has excellent mechanical properties, and has stable and efficient wear resistance and aging resistance, and has important application value in the technical field of ball mill linings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ball mill linings, and in particular relates to a ball mill lining and a processing technology thereof. Background Art

[0002] A ball mill is a type of grinding equipment that grinds materials into fine powder through the friction and collision between grinding balls mixed with materials. It has important applications in industries such as mining, chemical industry, and metallurgy.

[0003] During the ball milling process, the grinding balls have a relatively large friction and impact force on the wall of the ball mill barrel. In order to protect the barrel from direct impact and friction of the grinding body and materials, a lining is required. At present, the lining used in the ball mill is mostly rubber lining. The rubber lining is used to contact the grinding body, and its wear resistance determines the service life of the rubber lining. However, the wear resistance of the rubber material itself is poor, so in order to ensure the service life, it is often designed to be thicker, but this also reduces the effective filling rate of the grinding material.

[0004] In addition to improving wear resistance, the aging resistance of rubber also affects the service life of rubber linings, so it also needs to be enhanced. The usual way to improve the aging resistance of rubber is to add antioxidants, but the common antioxidants on the market have poor compatibility with the rubber matrix, which will cause "frosting". The "frosting" phenomenon is that the small molecule processing aids in the mixed rubber migrate in the matrix and form a layer of frost-like precipitates on the surface of the product. It not only affects the performance of the rubber, but also the appearance. Therefore, it is urgent to invent a ball mill lining that can solve the above problems to meet the higher demands in the field of ball mill lining technology. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a ball mill lining and a processing technology thereof.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A processing technology for a ball mill lining comprises the following steps:

[0008] Add styrene-butadiene rubber into an internal mixer at a temperature of 80-90°C, add modified nano silicon nitride, zinc oxide, initiator and lubricant after mixing for 2 minutes, and continue mixing at 130-150°C for 5-10 minutes. After mixing is completed, add sulfur (vulcanizing agent) and vulcanization accelerator for plate vulcanization to obtain the ball mill lining.

[0009] Furthermore, the raw materials are calculated in parts by weight as follows: 80-100 parts of styrene-butadiene rubber, 10-20 parts of modified nano silicon nitride, 4-8 parts of zinc oxide, 0.2-0.4 parts of initiator, 2-6 parts of lubricant, 3-5 parts of sulfur, and 0.5-1 parts of vulcanization accelerator.

[0010] Furthermore, the initiator is one of benzoyl peroxide and lauroyl peroxide.

[0011] Furthermore, the lubricant is one of zinc stearate, magnesium stearate and paraffin.

[0012] Furthermore, the vulcanization accelerator is one of 2-mercaptobenzothiazole and dibenzothiazole disulfide.

[0013] Taking styrene butadiene rubber as the matrix, the performance of styrene butadiene rubber is close to that of natural rubber, but it has better wear resistance, aging resistance and heat resistance; the addition of zinc oxide can make the lining after vulcanization have higher mechanical properties; the vulcanization accelerator is a thiazole vulcanization accelerator, which can effectively shorten the vulcanization time, lower the vulcanization temperature, reduce the amount of vulcanizer and improve the mechanical properties of the lining.

[0014] Furthermore, the modified nano silicon nitride is prepared by the following steps:

[0015] S1. Add methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, thiodiethanol, lithium diisopropylamide (catalyst, LAD) and N,N-dimethylformamide (DMF) into a three-necked flask equipped with a stirring device, stir and mix evenly, pass nitrogen to remove air, heat to 80°C, keep warm for 8 hours, and after the reaction is completed, remove the solvent by vacuum distillation, wash with anhydrous ethanol 2-3 times to obtain intermediate 1; the amount ratio of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, thiodiethanol, lithium diisopropylamide and N,N-dimethylformamide is 29.2g:13.7g:0.2g:150mL;

[0016] Under the catalysis of lithium diisopropylamide, methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and thiodiethanol undergo an ester exchange reaction. By controlling the molar ratio of the two to be close to 1:1 and the thiodiethanol to be slightly excessive, only one hydroxyl group on the thiodiethanol participates in the reaction to obtain intermediate 1. The specific reaction process is as follows:

[0017]

[0018] S2. After trimesic acid, 4-pentene-1-ol and toluene are mixed in a three-necked flask equipped with a stirring device, dicyclohexylcarbodiimide (DCC, dehydrating agent) and 4-dimethylaminopyridine (DMAP, catalyst) are added in sequence, the reaction temperature is controlled to 75°C, and the reaction is stirred for 8 hours. After the reaction is completed, part of the solvent is first removed by rotary evaporation, and then purified by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two is 1:2), and the eluent is removed by rotary evaporation to obtain intermediate 2; the ratio of trimesic acid, 4-pentene-1-ol, toluene, dicyclohexylcarbodiimide and 4-dimethylaminopyridine is 22.1g:8.6g:150mL:20.6g:0.4g;

[0019] Under the catalysis of DCC and DMAP, the carboxyl group on trimesic acid and the hydroxyl group on 4-penten-1-ol undergo esterification reaction. By controlling the molar ratio of the two to be close to 1:1 and the trimesic acid to be slightly excessive, only one carboxyl group on the trimesic acid participates in the reaction to obtain intermediate 2. The specific reaction process is shown below:

[0020]

[0021] S3. After mixing intermediate 1 and intermediate 2 with N,N-dimethylformamide in a three-necked flask equipped with a stirring device, dicyclohexylcarbodiimide and 4-dimethylaminopyridine were added in sequence, the reaction temperature was controlled to 85°C, and the reaction was stirred for 12 hours. After the reaction was completed, part of the solvent was first removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:3), and the eluent was removed by rotary evaporation to obtain a modifier; the ratio of the amount of intermediate 1, intermediate 2, N,N-dimethylformamide, dicyclohexylcarbodiimide, and 4-dimethylaminopyridine was 38.2g:28.6g:150mL:20.6g:0.4g;

[0022] The carboxyl group on the intermediate 2 and the hydroxyl group on the intermediate 1 undergo an esterification reaction. By controlling the molar ratio of the two to be close to 1:1 and the intermediate 2 to be slightly excessive, only one carboxyl group on the intermediate 2 participates in the reaction to obtain a modifier. The specific reaction process is as follows:

[0023]

[0024] S4. Add nano silicon nitride and N,N-dimethylformamide to a three-necked flask, stir magnetically for 4 hours to make the nano silicon nitride evenly dispersed, then add modifier and 4-dimethylaminopyridine, start stirring, react at 80°C for 6 hours, and after the reaction is completed, filter out the residue, vacuum dry, and grind to obtain modified nano silicon nitride; the ratio of nano silicon nitride, N,N-dimethylformamide, modifier, and 4-dimethylaminopyridine is 1g:100mL:8.4g:0.3g;

[0025] The surface of nano silicon nitride contains a large number of hydroxyl groups and amino groups, which can react with the carboxyl groups in the modifier molecules under the action of catalysts to obtain modified nano silicon nitride;

[0026] Nano silicon nitride is a ceramic powder with excellent performance, good high temperature strength, high fracture strength and excellent friction and wear resistance. The modifier is grafted and coated on the surface of nano silicon nitride to form an organic layer on its surface, which greatly improves the interface effect between nano silicon nitride and styrene-butadiene rubber matrix, improves the compatibility between the two, reduces the agglomeration of nano silicon nitride, and evenly disperses nano silicon nitride in the matrix, so that the performance of nano silicon nitride is fully exerted, and the wear resistance and mechanical strength of the matrix are greatly enhanced; in addition, the modified nano silicon nitride also contains thioesters, hindered phenols, benzene rings and carbon-carbon double bond structures. Among them, thioester, as an antioxidant, can improve the anti-aging performance of the matrix to a certain extent; the introduced hindered phenol can provide active hydrogen atoms, capture peroxyl radicals, and can synergize with thioester to greatly improve the anti-aging performance of the matrix. Not only that, the thioether group can also improve the mechanical properties of the polypropylene matrix; in addition, the introduced benzene ring is hydrophobic, and styrene-butadiene rubber contains benzene rings, which can further enhance the compatibility of nano-silicon nitride with the matrix; finally, the introduced carbon-carbon double bond can cross-link with the matrix, enhance the interaction force with the matrix, reduce the occurrence of blooming, and improve the stability of modified nano-silicon nitride;

[0027] It should be noted that the grafted coating of the modifier with nano-silicon nitride can make it difficult for the modifier to migrate and seep out, thereby improving the stability of the modifier and further reducing the frosting phenomenon.

[0028] Beneficial effects of the present invention:

[0029] 1. The lining prepared by the present invention uses styrene-butadiene rubber as a matrix, which gives the lining certain wear resistance and aging resistance;

[0030] 2. The added zinc oxide can improve the mechanical properties of the lining after vulcanization;

[0031] 3. The added vulcanization accelerator can shorten the vulcanization time, lower the vulcanization temperature, reduce the amount of vulcanizing agent, and improve the mechanical properties of the lining;

[0032] 4. By modifying nano silicon nitride, compared with ordinary nano silicon nitride, it has better compatibility with styrene-butadiene rubber matrix, significantly improves the wear resistance, anti-aging and mechanical properties of the lining, and has stable performance, and the frosting phenomenon is significantly reduced;

[0033] Therefore, the lining prepared by the present invention has excellent mechanical properties, and has stable and efficient wear resistance and anti-aging properties, and has important application value in the field of ball mill lining technology. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Embodiment 1

[0036] Preparation of modified nano silicon nitride:

[0037] S1. Add 29.2 g of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 13.7 g of thiodiethanol, 0.2 g of lithium diisopropylamide and 150 mL of N,N-dimethylformamide into a three-necked flask equipped with a stirring device, stir and mix evenly, pass nitrogen to remove all air, heat to 80° C., keep warm for 8 hours, and after the reaction is completed, remove the solvent by distillation under reduced pressure, wash twice with anhydrous ethanol to obtain intermediate 1;

[0038] S2, in a three-necked flask equipped with a stirring device, 22.1 g of trimesic acid, 8.6 g of 4-penten-1-ol and 150 mL of toluene were mixed, and then 20.6 g of dicyclohexylcarbodiimide and 0.4 g of 4-dimethylaminopyridine were added in sequence, the reaction temperature was controlled to 75°C, and the reaction was stirred for 8 hours. After the reaction was completed, part of the solvent was first removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 1:2), and the eluent was removed by rotary evaporation to obtain intermediate 2;

[0039] S3, in a three-necked flask equipped with a stirring device, 38.2g of intermediate 1, 28.6g of intermediate 2 and 150mL of N,N-dimethylformamide were mixed, and 20.6g of dicyclohexylcarbodiimide and 0.4g of 4-dimethylaminopyridine were added in sequence, the reaction temperature was controlled to 85°C, and the reaction was stirred for 12h. After the reaction was completed, part of the solvent was first removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:3), and the eluent was removed by rotary evaporation to obtain a modifier;

[0040] S4. Add 1 g of nano silicon nitride and 100 mL of N,N-dimethylformamide to a three-necked flask, stir magnetically for 4 h to evenly disperse the nano silicon nitride, then add 8.4 g of a modifier and 0.3 g of 4-dimethylaminopyridine, start stirring, and react at 80 °C for 6 h. After the reaction is complete, filter out the residue, dry it in vacuum, and grind it to obtain modified nano silicon nitride.

[0041] Embodiment 2

[0042] Preparation of modified nano silicon nitride:

[0043] S1. Add 58.4 g of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 27.4 g of thiodiethanol, 0.4 g of lithium diisopropylamide and 300 mL of N,N-dimethylformamide into a three-necked flask equipped with a stirring device, stir and mix evenly, pass nitrogen to remove all air, heat to 80° C., keep warm for 8 hours, and after the reaction is completed, remove the solvent by distillation under reduced pressure, wash 3 times with anhydrous ethanol to obtain intermediate 1;

[0044] S2, in a three-necked flask equipped with a stirring device, 44.2 g of trimesic acid, 17.2 g of 4-penten-1-ol and 300 mL of toluene were mixed, and then 41.2 g of dicyclohexylcarbodiimide and 0.8 g of 4-dimethylaminopyridine were added in sequence, and the reaction temperature was controlled to 75°C, and the reaction was stirred for 8 hours. After the reaction was completed, part of the solvent was first removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 1:2), and the eluent was removed by rotary evaporation to obtain intermediate 2;

[0045] S3. In a three-necked flask equipped with a stirring device, 76.4 g of intermediate 1, 57.2 g of intermediate 2 and 300 mL of N, N-dimethylformamide were mixed, and then 41.2 g of dicyclohexylcarbodiimide and 0.8 g of 4-dimethylaminopyridine were added in sequence. The reaction temperature was controlled to 85°C, and the reaction was stirred for 12 hours. After the reaction was completed, part of the solvent was first removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:3), and the eluent was removed by rotary evaporation to obtain a modifier;

[0046] S4. Add 2 g of nano silicon nitride and 200 mL of N,N-dimethylformamide into a three-necked flask, stir magnetically for 4 h to evenly disperse the nano silicon nitride, then add 16.8 g of a modifier and 0.6 g of 4-dimethylaminopyridine, start stirring, and react at 80 °C for 6 h. After the reaction is complete, filter out the residue, dry it in vacuum, and grind it to obtain modified nano silicon nitride.

[0047] Embodiment 3

[0048] 80g of styrene-butadiene rubber was added to an internal mixer at a temperature of 80°C. After mixing for 2 minutes, 10g of the modified nano-silicon nitride prepared in Example 1, 4g of zinc oxide, 0.2g of benzoyl peroxide and 2g of zinc stearate were added. Mixing was continued at 130°C for 5 minutes. After mixing was completed, 3g of sulfur and 0.5g of 2-thiolbenzothiazole were added for plate vulcanization to obtain a ball mill lining.

[0049] Embodiment 4

[0050] 90 g of styrene-butadiene rubber was added to an internal mixer at a temperature of 85° C. After mixing for 2 min, 15 g of modified nano silicon nitride obtained in Example 2, 6 g of zinc oxide, 0.3 g of lauroyl peroxide and 4 g of magnesium stearate were added, and mixing was continued at 140° C. for 7 min. After mixing was completed, 4 g of sulfur and 1 g of dibenzothiazole disulfide were added for plate vulcanization to obtain a ball mill lining.

[0051] Embodiment 5

[0052] 100 g of styrene-butadiene rubber was added to an internal mixer at a temperature of 90° C. After mixing for 2 min, 20 g of the modified nano silicon nitride obtained in Example 2, 8 g of zinc oxide, 0.4 g of lauroyl peroxide and 6 g of paraffin were added, and mixing was continued at 150° C. for 10 min. After mixing was completed, 5 g of sulfur and 1 g of dibenzothiazole disulfide were added for plate vulcanization to obtain a ball mill lining.

[0053] Comparative Example 1

[0054] Ordinary nano silicon nitride of the same mass is used to replace the modified nano silicon nitride in Example 5, and the remaining steps are the same as those in Example 5 to prepare the lining.

[0055] Comparative Example 2

[0056] Use commercially available wear-resistant rubber.

[0057] Embodiments 3, 4, 5, and comparative examples 1 and 2 were made into corresponding shapes according to different test standards, and the following performance tests were performed:

[0058] The tensile strength is determined using the national standard GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber";

[0059] The tearing properties are measured using the national standard GB / T 529-2008 "Determination of tear strength of vulcanized rubber or thermoplastic rubber";

[0060] The wear volume is measured using the national standard GB / T 25262 "Guide to abrasion testing of vulcanized rubber or thermoplastic rubber";

[0061] The national standard GB / T 3511-2001 "Direct natural climate aging test method for vulcanized rubber or thermoplastic rubber" is used to measure the tensile strength and wear resistance of the sample after 6 months of outdoor aging;

[0062] The measured results are shown in the following table:

[0063]

[0064] It can be seen from the above table that the lining prepared in the embodiment of the present invention has better mechanical, wear-resistant and anti-aging properties than the control example, and the performance is long-lasting and stable, and has important application value in the field of ball mill lining technology.

[0065] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0066] The above contents are merely examples and explanations of the present invention. Any modifications or additions made by technicians in the technical field to the described specific embodiments or replacements with similar methods shall all fall within the protection scope of the present invention.

Claims

1. A process for processing a ball mill lining, characterized in that: The following steps are involved: Add styrene-butadiene rubber into an internal mixer, add modified nano silicon nitride, zinc oxide, an initiator and a lubricant, continue mixing, and after mixing is completed, add sulfur and a vulcanization accelerator to perform plate vulcanization to obtain a ball mill lining; Wherein, the modified nano silicon nitride is prepared by the following steps: S1. Methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, thiodiethanol, lithium diisopropylamide and N,N-dimethylformamide were stirred and mixed uniformly, and then nitrogen was passed to remove all air. The temperature was raised to 80° C. and the reaction was kept warm for 8 hours. After the reaction was completed, the mixture was distilled under reduced pressure and washed to obtain intermediate 1; the ratio of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, thiodiethanol, lithium diisopropylamide and N,N-dimethylformamide was 29.2 g:13.7 g:0.2 g:150 mL; S2, after trimesic acid, 4-penten-1-ol and toluene are mixed, dicyclohexylcarbodiimide and 4-dimethylaminopyridine are added in sequence, and the mixture is stirred at 75°C for 8 hours. After the reaction is completed, the mixture is rotary evaporated, purified by column chromatography, and rotary evaporated to obtain intermediate 2; the ratio of trimesic acid, 4-penten-1-ol, toluene, dicyclohexylcarbodiimide and 4-dimethylaminopyridine is 22.1 g: 8.6 g: 150 mL: 20.6 g: 0.4 g; S3, after mixing intermediate 1 and intermediate 2 with N,N-dimethylformamide, dicyclohexylcarbodiimide and 4-dimethylaminopyridine were added in sequence, and the mixture was stirred at 85°C for 12 hours. After the reaction was completed, the mixture was rotary evaporated, purified by column chromatography, and rotary evaporated to obtain a modifier; the ratio of the amount of intermediate 1, intermediate 2, N,N-dimethylformamide, dicyclohexylcarbodiimide, and 4-dimethylaminopyridine was 38.2 g: 28.6 g: 150 mL: 20.6 g: 0.4 g; S4. Add nano silicon nitride and N,N-dimethylformamide to a three-necked flask, stir magnetically for 4 hours to make the nano silicon nitride evenly dispersed, then add modifier and 4-dimethylaminopyridine, start stirring, react at 80°C for 6 hours, and after the reaction is completed, filter out the residue, vacuum dry, and grind to obtain modified nano silicon nitride; the ratio of nano silicon nitride, N,N-dimethylformamide, modifier, and 4-dimethylaminopyridine is 1g:100mL:8.4g:0.3g; The raw materials are calculated in parts by weight as follows: 80-100 parts of styrene-butadiene rubber, 10-20 parts of modified nano silicon nitride, 4-8 parts of zinc oxide, 0.2-0.4 parts of initiator, 2-6 parts of lubricant, 3-5 parts of sulfur, and 0.5-1 parts of vulcanization accelerator.

2. A ball mill lining processing technology according to claim 1, characterized in that: The vulcanization accelerator is one of 2-mercaptobenzothiazole and dibenzothiazole disulfide.

3. A ball mill lining, characterized in that: Prepared according to the processing technology according to any one of claims 1-2.

Citation Information

Patent Citations

  • Light wear-resistant ball mill rubber lining composition and preparation method thereof

    CN111533963A

  • Synthesis method of thioether phenolic antioxidant

    CN112279792A